Population Status of Michelia citrata in Cao Ta Tung Forest, Quan Ba District, Ha Giang Province - Ngan, Tu Bao; Hieu, Nguyen Quang; Hiep, Nguyen Tien; Long, Phan Ke; Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 1, 2018)
Michelia citrata is one of threatened species in Vietnam. It grows in subtropical evergreen broadleaved and coniferous forests at elevations higher than 1000m in Ha Giang province. In Cao Ta Tung forest, Quan Ba district, Ha Giang province, the distribution of 33 individuals of Michelia citrata is scattered with low regeneration rate and mature trees threatened by firewood and planting Cardamom. Keywords Magnoliaceae, Michelia citrata , Ha Giang, Vietnam References [1]. Malin Rivers, Emily Beech, Lydia Murphy and Sara Oldfield, The Red list of Magnoliaceae, revised and extended, BGCI, Richmond, UK, 2016. [2]. Vu Quang Nam, Taxonomic Revision of the Family Magnoliaceae from Vietnam, Thesis of Doctorate, Graduate University of The Chinese Academy of Sciences. Guangzhou, 2011. [3]. Từ Bảo Ngân, Nghiên cứu sự phân bố, sinh thái, sinh học và hiện trạng bảo tồn của loài Giổi chanh (Michelia citrata (Noot. & Chalermglin) Q. N. Vu & N. H. Xia) tại xã Tùng Vài, huyện Quản Bạ, tỉnh Hà Giang, Luận văn Thạc sĩ, Trường Đại học Khoa học Tự nhiên, ĐHQGHN, 2014. [4]. Chalermglin P. and H. P. Nooteboom, A new species of and a new combination in Magnolia (Magnoliaceae), Blumea, 52, 2007: 559-562. [5]. Nguyễn Quang Hiếu, Nguyễn Tiến Hiệp, Từ Bảo Ngân, Nguyễn Sinh Khang, Kết quả nghiên cứu bước đầu về thành phần loài thuộc họ Ngọc lan (Magnoliaceae Juss.) tại tỉnh Hà Giang và đánh giá tình trạng bảo tồn của chúng, Hội nghị Khoa học toàn quốc lần thứ sáu về Sinh thái và Tài nguyên sinh vật, Viện Sinh thái và Tài nguyên sinh vật, Hà Nội, 2015: 130-136. [6]. Vũ Quang Nam, Xia Nianhe, Bổ sung loài Michelia citrata (Noot. & Chalermglin) Q. N. Vu & N. H. Xia (họ Mộc lan - Magnoliaceae Juss.) cho hệ thực vật Việt Nam, Tạp chí sinh học, 33(4), 2011: 42-44. [7]. Nooteboom H. P. and P. Chalermglin, The Magnoliaceae of Thailand, Thai For. Bull. (Bot.). 37, 2009, 121. [8]. Nguyễn Nghĩa Thìn, Các phương pháp nghiên cứu thực vật, NXB Đại học Quốc gia Hà Nội, Hà Nội, 2007. [9]. UBND tỉnh Hà Giang, Báo cáo tổng hợp Quy hoạch bảo tồn Đa dạng sinh học tỉnh Hà Giang đến năm 2020, định hướng đến năm 2030” kèm theo QĐ số 1589/QĐ-UBND ngày 27/8/2015 của UBND tỉnh Hà Giang về việc Phê duyệt Quy hoạch bảo tồn Đa dạng sinh học tỉnh Hà Giang đến năm 2020, định hướng đến năm 2030, 2015.